Model of the Oxygen Cutting Taking into Account the Melting of Metal; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Anisimova M. A. Mariya Aleksandrovna (Simulation of Physical and Chemical Processes, 2014)
Title screen